Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12889-015-1448-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health risk reduction interventions for people with severe mental illness: a systematic review

Abstract: BackgroundDespite variability in sexual activity among people with severe mental illness, high-risk sexual behavior (e.g. unprotected intercourse, multiple partners, sex trade and illicit drug use) is common. Sexual health risk reduction interventions (such as educational and behavioral interventions, motivational exercises, counselling and service delivery), developed and implemented for people with severe mental illness, may improve participants’ knowledge, attitudes, beliefs behaviors or practices (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 50 publications
0
27
0
6
Order By: Relevance
“…Also, patients with severe mental disorders frequently have risky sexual behaviors, which are often due to the presence of cognitive deficits and manic symptoms, and represent the cause of many sexual transmitted diseases. Moreover, the sexual health of patients with severe mental disorders is often neglected by clinicians who do not routinely ask to patients about their sexual life ( 75 , 76 ). The circadian rhythms are frequently altered due to polarity switch of mood in affective disorders or to the non-adherence to psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with severe mental disorders frequently have risky sexual behaviors, which are often due to the presence of cognitive deficits and manic symptoms, and represent the cause of many sexual transmitted diseases. Moreover, the sexual health of patients with severe mental disorders is often neglected by clinicians who do not routinely ask to patients about their sexual life ( 75 , 76 ). The circadian rhythms are frequently altered due to polarity switch of mood in affective disorders or to the non-adherence to psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that psychiatric symptoms are often not the direct cause of sex risk behavior; instead, indirect socioeconomic factors like financial instability and partner violence [11] and individual characteristics such as substance use and attitudes toward sex [8, 10] may drive sex risk behavior. There are a number of effective interventions to reduce sex risk among this population in the short term, but research assessing sustained effects is needed [19, 20]. Future studies could better assess the effectiveness of these interventions by implementing more rigorous randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Two reviews evaluated the effectiveness of these interventions for improving sex risk behavior, knowledge, and attitudes [19, 20]. The number of intervention sessions was quite variable, ranging from 3 to 15.…”
Section: Primary Hiv Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPHPP was developed to be suitable for evaluating a range of study designs including randomized clinical trials (RCTs) and observational studies. The instrument has been used in multiple systematic reviews see 3437 relevant to mental health treatment and has demonstrated content and construct validity. 38, 39 This is the first systematic review to adapt the EPHPP to evaluate studies of DTCA.…”
Section: Methodsmentioning
confidence: 99%